Early Cardiotoxicity after Adjuvant Concomitant Treatment with Radiotherapy and Trastuzumab in Patients with Breast Cancer - Marinko, Tanja (Radiol Oncol, 2018)
BACKGROUND: The purpose of the study was to find out whether there is a difference in the early parameters of cardiotoxicity (left ventricular ejection fraction [LVEF] and N-terminal pro-B-type natriuretic peptide [NT-proBNP]) between the two groups of patients: the patients treated for left breast cancer (left breast cancer group) and those treated for the right breast cancer (right breast cancer group), after the treatment had been completed. PATIENTS AND METHODS: The study included 175 consecutive patients with human epidermal growth factor receptor-2 (HER2) positive early breast cancer, treated concurrently with trastuzumab and radiotherapy (RT), between June 2005 and December 2010. Echocardiography with LVEF measurement was performed before adjuvant RT (LVEF(0)) and after the completed treatment (LVEF(1),). After the treatment NT-proBNP measurement was done as well. The difference (Δ) between LVEF(0) and LVEF(1) was analysed (Δ LVEF = LVEF(0) - LVEF(1)) and compared between the two groups. RESULTS: There were 84 patients in the left and 91 in the right breast cancer group. Median observation time was 57 (37–71) months. Mean Δ LVEF (%) was -1.786% in the left and -2.607% in the right breast cancer group (p = 0.562, CI: -2.004 to 3.648). Median NT-proBNP were 111.0 ng/l in the left and 90.0 ng/l in the right breast cancer group (p = 0.545). Echocardiography showed that the patients in the left breast cancer group did not have significantly worse systolic and diastolic left ventricular function in comparison with the patients in the right breast cancer group, but, they had higher incidence of pericardial effusion (9 [11%] vs. 1 [1%]) (p = 0.007). CONCLUSIONS: We did not find any significant differences in the early parameters of cardiotoxicity (LVEF, NT-proBNP) between the observed groups. Patients who received left breast/chest wall irradiation had higher incidence of pericardial effusion.